EVALUASI PELAKSANAAN KEBIJAKAN SISTEM INFORMASI DAN MANAJEMEN PERTANAHAN NASIONAL (SIMTANAS) DI KANTOR PERTANAHAN KABUPATEN PELALAWAN - Syaprianto, Syaprianto (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2018)
This study aims to evaluate the implementation of the Sistem Informasi dan Manajemen Pertanahan Nasional (SIMTANAS) policy at the Land Office in Pelalawan District and this research was carried out using survey research methods, the level of exploration was descriptive and using qualitative data analysis. The researcher interviewed directly and deeply to the key informants who were considered to know about the Implementation of the Sistem Informasi dan Manajemen Pertanahan Nasional (SIMTANAS) policy using technique snowball. The results of this study indicate that the Evaluation of implementation of the Sistem Informasi dan Manajemen Pertanahan Nasional (SIMTANAS) at the Land Office in Pelalawan District been implemented are optimal in providing services to the community, but there are some research findings that must be repaired by the Land Office in Pelalawan District. First, Quality of resources related to operational information systems and land management must be improved by providing training. Second, facilities and infrastructure must support in order to create excellent service because there are still facilities and infrastructure that are problematic when providing services to the community.